Percepções e vivências de mulheres acerca da humanização no parto normal - GOMES, Ana Carolina de Sousa (2019)
INTRODUCTION: Pregnancy and childbirth are singular processes, unique and special experiences in the universe of the woman and her partner, which also involve their families and the community in which they are inserted. A time filled with many feelings, among them, love, satisfaction, fear, insecurity, many doubts, in which a quality assistance is essential to attend this woman in a humanized way, respecting and asserting their rights. The study emphasizes, through the experiences of women, the importance of humanization in normal childbirth, aiming to reinforce the benefits of this assistance, already recommended by the World Health Organization and Ministry of Health, in addition to clarifying and strengthening the rights of these women, Which are often unknown and / or unrealized, so that they do not receive a humanized care in their labor and delivery, and thus the lack of information and guidance throughout the pregnancy cycle, turns them into mere spectators in their parturition process. OBJECTIVES: To describe the perceptions and experiences of women about humanization in childbirth and normal childbirth and to learn the knowledge of these women about humanized childbirth and its implications during childbirth and childbirth through their experiences. METHOD: a descriptive study with a qualitative approach was carried out in the Accommodation Conjunct (ALCON) of the Santa Casa of Misericordia Foundation of Pará (FSCMPA), with 16 women in a normal postpartum period, through a semi-structured interview. RESULTS: They were constructed from a central directing core, generating five categories of analysis: 1) Humanized childbirth: knowledge vs. ignorance; 2) The importance of guidance in the puerperal pregnancy cycle: the path from prenatal to the process of childbirth and birth; 3) Practices in attention to childbirth and birth: humanization under the perspectives of puerperae; 4) The importance of the link with health professionals in the context of the parturition process with a view to humanization; 5) Violence in obstetric care in the perception of women: the inverse path to humanization at childbirth. Several practices were mentioned by the women related to the experiences of humanization in childbirth, among them the presence of the companion, the skin-to-skin contact with the RN at birth. The freedom of position and movement, the use of non-pharmacological methods of pain relief, and normal childbirth proper as the preferred delivery method. FINAL CONSIDERATIONS: In order for humanized childbirth to actually be exercised within health institutions, it is necessary to change professional care, with a great focus on prenatal care, where women can have quality, clear and objective assistance, clarifying their doubts and strengthening their rights, preparing them for labor, childbirth and maternity. Considering that, based on the recognition of her rights, she has understanding and autonomy in her parturition process.